I hear a pickle : (and smell, see, touch, and taste it, too!) - Isadora, Rachel (New York, NY : Nancy Paulsen Books, an imprint of Penguin Group (USA), 2016)
Children explore their five senses, learning what they can see, smell, hear, touch, and taste.
Keywords: Senses and sensation -- Juvenile fiction; Perception -- Juvenile fiction; Senses and sensation -- Fiction; Vision -- Fiction; Hearing -- Fiction; Taste -- Fiction; Smell -- Fiction; Touch -- Fiction